Bangla validation of the smartphone addiction scale and the academic underachievement scale: The associative role of classroom mindful attention in the relationship between smartphone addiction and underachievement among adolescents and young adults - Shakira Khatun; Md. Mehedi Hassan Ridoy; Abu Hanif Noman; Md. Muazzem Hosen Sharon; Md. Rahim Mia; Jahedul Islam; Sajedul Hasan Himel; Mohd. Ashik Shahrier (PLoS ONE, 2026)
This study aimed to validate the Smartphone Addiction Scale–Short Version (SAS-SV) and the Perceived Academic Underachievement Scale (PAUS) for Bangladeshi adolescents and young adults. In addition, the study investigated whether classroom mindful attention has an indirect association with the relationship between smartphone addiction and academic underachievement in the target population. A cross-sectional survey using convenience sampling was conducted with 712 participants recruited from different educational institutions in Bangladesh. Bangla versions of SAS-SV, Classroom Mindful Attention Regulation Scale, and PAUS were administered in collecting data. Factor structure, reliability, and validity of the measures were assessed, and statistical mediation to determine the indirect association was conducted to achieve the study aims. Both SAS-SV and PAUS showed excellent internal consistency (Cronbach’s α = 0.95 and 0.91, respectively) and confirmed the predefined factor structures with good model fits (CFI = 0.99, TLI = 0.99, RMSEA = 0.05, SRMR = 0.03; PAUS: CFI = 0.99, TLI = 0.99, RMSEA = 0.04, SRMR = 0.03). While determining the convergent validity of the measures, both smartphone addiction and perceived academic underachievement were associated with lower GPAs and reduced classroom mindful attention. Moreover, the SAS-SV and PAUS were found to be invariably applicable across age, gender, and data collection mode. Mediation analyses indicate that the self-awareness component of classroom mindful attention had an indirect association with the relationship between smartphone addiction and perceived academic underachievement in young adults ( B = 0.014, 95% CI [0.001, 0.028], p = .033) and the combined sample ( B = 0.020, 95% CI [0.005, 0.036], p = .009), whereas no significant indirect association was observed among adolescents. These findings highlight the associative role of classroom self-awareness in the relationship between smartphone addiction and perceived academic underachievement and underscore the potential role of mindfulness-based interventions in educational settings.